First trimester genetic sonogram for screening fetal Down syndrome: A population-based study - Kuntharee Traisrisilp; Supatra Sirichotiyakul; Fuanglada Tongprasert; Kasemsri Srisupundit; Suchaya Luewan; Phudit Jatavan; Sirinart Sirilert; Theera Tongsong (Elsevier, 2021)
Objective: To evaluate the performance of first trimester sonomarkers in the detection of fetal Down syndrome among Thai pregnant women. Materials and methods: Pregnant women at 11-13+6 weeks' gestation underwent ultrasound examination for assessment of nuchal translucency (NT), nasal bone (NB), tricuspid regurgitation (TR), and abnormal ductus venosus (aDV) Doppler waveforms. The women were followed up for final outcomes. Fetal abnormalities other than trisomy 21 were excluded. The performances of each sonomarker and their combinations in predicting fetal Down syndrome were calculated. Results: A total of 7820 pregnant women meeting the inclusion criteria were available for analysis, including 20 cases with fetal Down syndrome and 7800 unaffected cases. Of the four sonomarkers, NT, as a single sonomarker, had the highest detection rate (55.0% at a false positive rate of about 5%), whereas the remaining single sonomarkers had low detection rate (15-20%). The combination of all sonomarkers had the highest detection rate of 70% but the false positive rate was as high as 10.8%. The combination of NT and NB had a detection rate of 60% with an acceptable false positive rate of 6.9%, whereas the other combinations yielded relatively high false positive rates. Conclusion: The first trimester genetic sonogram in screening for Down syndrome among Asian women is acceptably effective and may be offered to some selected groups of the population. NT is the best sonomarker with a detection rate of 55% at 5% false positive rate and its combination with NB can improve performance with minimal increase in false positive rate.